RepSox Slows Decay of CD34+ Acute Myeloid Leukemia Cells and Decreases T Cell Immunoglobulin Mucin-3 Expression. (22nd May 2014) - Jajosky, Audrey N.; Coad, James E.; Vos, Jeffrey A.; Martin, Karen H.; Senft, Jamie R.; Wenger, Sharon L.; Gibson, Laura F.
Abstract : To facilitate development of therapies that target leukemic stem/progenitor cells (LPCs), in vitro ways to enhance the survival and immunogenicity of a patient's CD34 + acute myeloid leukemia (AML) cells were explored. RepSox was identified as a candidate cell-engineering tool because it slows in vitro decay of CD34 + AML cells (which often contain LPCs) and accelerates loss of the immune checkpoint receptor T cell immunoglobulin mucin-3 (Tim-3). Abstract: : Despite initial response to therapy, most acute myeloid leukemia (AML) patients relapse. To eliminate relapse-causing leukemic stem/progenitor cells (LPCs), patient-specific immune therapies may be required. In vitro cellular engineering may require increasing the "stemness" or immunogenicity of tumor cells and activating or restoring cancer-impaired immune-effector and antigen-presenting cells. Leukapheresis samples provide the cells needed to engineer therapies: LPCs to be targeted, normal hematopoietic stem cells to be spared, and cancer-impaired immune cells to be repaired and activated. This study sought to advance development of LPC-targeted therapies by exploring nongenetic ways to slow the decay and to increase the immunogenicity of primary CD34 + AML cells. CD34 + AML cells generally displayed more colony-forming and aldehyde dehydrogenase activity than CD34 − AML cells. Along with exposure to bone marrow stromal cells and low (1%–5%) oxygen, culture with RepSox (a reprogramming tool and inhibitor of transforming growth factor-β receptor 1) consistently slowed decline of CD34 + AML and myelodysplastic syndrome (MDS) cells. RepSox-treated AML cells displayed higher CD34, CXCL12, and MYC mRNA levels than dimethyl sulfoxide-treated controls. RepSox also accelerated loss of T cell immunoglobulin mucin-3 (Tim-3), an immune checkpoint receptor that impairs antitumor immunity, from the surface of AML and MDS cells. Our results suggest RepSox may reduce Tim-3 expression by inhibiting transforming growth factor-β signaling and slow decay of CD34 + AML cells by increasing CXCL12 and MYC, two factors that inhibit AML cell differentiation. By prolonging survival of CD34 + AML cells and reducing Tim-3, RepSox may promote in vitro immune cell activation and advance development of LPC-targeted therapies.